Beyond Usability in Games - Pagulayan, Randy; Steury, Keith (ACM Interactions, 2004)
Video games are an art form that combines traditional artistic endeavors such as the visual arts, story-telling, and music, with more modern technical and engineering achievements. At the center of this effort is the game designer who drives the creative vision and who decides what needs to be accomplished in the design and creation of the video game. At some level, we, as user researchers, can provide input at nearly every stage of the development process that is useful for design, but in the end, it is not up to us to design a game. Our role is to assist…